Atypical CIDP: diagnostic criteria, progression and treatment response. Data from the Italian CIDP Database. Issue 2 (8th October 2018) - Doneddu, Pietro Emiliano; Cocito, Dario; Manganelli, Fiore; Fazio, Raffaella; Briani, Chiara; Filosto, Massimiliano; Benedetti, Luana; Mazzeo, Anna; Marfia, Girolama Alessandra; Cortese, Andrea; Fierro, Brigida; Jann, Stefano; et al.
Abstract : Objectives: A few variants of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) have been described, but their frequency and evolution to typical CIDP remain unclear. To determine the frequency and characteristics of the CIDP variants, their possible evolution to typical CIDP, and treatment response. Methods: We applied a set of diagnostic criteria to 460 patients included in a database of Italian patients with CIDP. Clinical characteristics and treatment response were reviewed for each patient. The Kaplan-Meier curve was used to estimate the progression rate from atypical to typical CIDP. Results: At the time of inclusion, 376 (82%) patients had a diagnosis of typical CIDP while 84 (18%) had atypical CIDP, including 34 (7%) with distal acquired demyelinating symmetric neuropathy (DADS), 17 (4%) with purely motor, 17 (4%) with Lewis-Sumner syndrome (LSS) and 16 (3.5%) with purely sensory CIDP. Based on retrospective review of the symptoms and signs present at onset and for at least 1 year, 180 (39%) patients had an initial diagnosis compatible with atypical CIDP that in 96 (53%) patients evolved to typical CIDP. Mean disease duration was longer in patients evolving to typical CIDP than in those not evolving (p=0.0016). Patients with DADS and LSS had a less frequent response to immunoglobulin than those with typical CIDP, while patients with purely motor and sensory CIDP had a similar treatment response. Conclusions: The proportion of patients with atypical CIDP varies during the disease course. DADS and LSS have a less frequent response to intravenous immunoglobulin compared with typical CIDP, raising the possibility of a different underlying pathogenetic mechanism.